Comparing the effect of landscape context on vascular plant and bryophyte communities in a human‐dominated landscape. (11th September 2020) - McCune, Jenny L.; Frendo, Christina J.; Ramadan, Mohammed; Baldwin, Lyn K.
Abstract: Aims: It is important to understand the effect of landscape context on biological communities to predict how biodiversity will be affected on human‐dominated landscapes. While many studies have tested the effects of landscape context on the species richness and composition of vascular plants, few have compared the responses of vascular plants and bryophytes on the same landscape. We sampled non‐epiphytic bryophytes and vascular plants in 184 plots to test whether three landscape context factors measured four years or four decades previously could predict bryophyte or vascular plant species richness and composition after accounting for local factors. Location: Temperate forests and oak savannahs, Vancouver Island, British Columbia, Canada. Methods: We used model selection and comparisons to test the effects of surrounding road density, total amount of forest, and distance to the nearest forest edge on species richness, species richness of non‐disturbance‐associated species, and community composition after controlling for important local predictors including substrate availability and topography. Results: The species richness of non‐disturbance‐associated vascular plants was lower in plots with greater surrounding historical road density, and perennial stayer bryophyte richness declined with increasing historical road density and lower historical forest amount, suggesting a potential extinction debt. Landscape context significantly affected total species richness and community composition of vascular plants, but not bryophytes. Conclusion: While bryophytes appear to be less sensitive overall to landscape context than vascular plants, disturbance‐intolerant perennial stayer bryophytes may decline in the future in response to the increased road density and loss of forest cover that has occurred over the past four decades. Abstract : We tested the effect of past and present landscape context on vascular plant and bryophyte communities on the Saanich Peninsula, Canada. Landscape context significantly affected total species richness and overall community composition of vascular plants, but not bryophytes. However, the richness of perennial stayer bryophytes was negatively correlated with the density of roads four decades in the past.